Path-analytic study of gender,mathatics conception, manipulative skills, learning readiness and students' achievement in mathematics (2011)
The world of science and technology will be without meaning in the absence of mathematics. Knowing the important roles knowledge of mathematics plays in the provision of amenities jar human convenience, learning of the subject should attract attention of researchers. This study therefore intended to use ive-variable models to explain students' achievement in mathematics. Fourteen senior secondary schools were randomly selected out of twenty-one public senior secondary schools in Ikorodu Local Government Area. Twenty five Senior Secondary II students were randomly selected from each school to give a total sample of 350 students. Four major items were used to collect data for this study. They were: Student's Conception Scale ( Cronbach alpha reliability coefficient = 0.83); Students' Readiness Scale ( cronbach alpha reliability coefficient = 0.86); Manipulative Skills Test (Spearman Brown reliability coefficient = 0.94) and Mathematics Achievement Test (Spearman Brown reliability coefficient = 0.71). The Results show that among the variables investigated, only Mathematics Learning readiness and manipulative skill had direct effects on Students' achievement in mathematics with (β=.654; p<. 05) and (β=-.114; p<.05) respectively. There were however, indirect effects of both exogenous and endogenous variables on students' achievement in Mathematics. Based on the findings of this study, it is recommended that teachers should support their students in acquiring high manipulative skills which will support their learning readiness for mathematics and enhance their achievements in the subject.